2012
DOI: 10.1080/1070289x.2012.734766
|View full text |Cite
|
Sign up to set email alerts
|

Grieving formestizaje: alternative approaches to Maya identity in Yucatan, Mexico

Abstract: This article takes as its point of departure the highly contested theoretical terrain of 'Maya' identity in Yucatan, Mexico. Set in the physical terrain of a state psychiatric hospital, this article uses a framework of identity culled from the narrative of a young woman, 'Claudina', committed to its wards, to argue that being 'in-between' categories of ethnic identity, an experience she characterises as a painful sense of ambiguous loss, can be fruitfully analysed using an analytical framework of ethnic identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…In my own work (c.f. Reyes‐Foster ), I found that the many Maya and non‐Maya speaking Yucatecans I talked to had bigger things to worry about than their non‐Maya identity or whether they were depicted as suicidal by the media. My interlocutors were mainly concerned with access to steady employment, financial security, and high‐quality medical care.…”
Section: The Specter Of IX Tabmentioning
confidence: 99%
See 2 more Smart Citations
“…In my own work (c.f. Reyes‐Foster ), I found that the many Maya and non‐Maya speaking Yucatecans I talked to had bigger things to worry about than their non‐Maya identity or whether they were depicted as suicidal by the media. My interlocutors were mainly concerned with access to steady employment, financial security, and high‐quality medical care.…”
Section: The Specter Of IX Tabmentioning
confidence: 99%
“…While Yucatán's Secretaría de Turismo (secretariat of tourism) has taken on the Ancient Maya as a cornerstone of its tourism industry, the ten‐year‐old Instituto para el Desarrollo de la Cultura Maya del Estado de Yucatán (INDEMAYA), the institute for the development of Maya culture of the state of Yucatán, has taken on the stated mission of creating a “new social order in which the Maya People may overcome the state of marginality and poverty in which it finds itself, and take its place in contemporary history” (INDEMAYA n.d.). It is beyond the scope of the present work to look at this aspect in detail, although the complexity of the “Maya” identity of Yucatán has been addressed by several scholars, for example, by Castañeda and Fallaw () in a special JLACA issue, as well as by Juan Castillo Cocom () and myself (Reyes‐Foster ). Nevertheless, I posit that the prevalence of the motif of Ix Tab in Yucatecan journalism cannot be understood without an awareness of the commercialization of the Ancient Maya and the ubiquity of public relations campaigns that encourage Maya‐speaking Yucatecan people to adopt a Maya identity they have never claimed before…”
Section: The Specter Of IX Tabmentioning
confidence: 99%
See 1 more Smart Citation
“…For an analysis of Maya identity, see Armstrong‐Fumero (). Reyes‐Foster () also offers a useful analysis in her work on contemporary Maya identity and mestizaje (the ideology of racial or cultural mixing of Spanish and Indigenous peoples).…”
mentioning
confidence: 99%
“…For a lively discussion of Yucatec Maya identity, including the role of physical appearance, see Castillo Cocom (), Reyes‐Foster (), and Ayora‐Diaz ().…”
mentioning
confidence: 99%